Ilusi Demokrasi Substansial di Indonesia: Sebuah Kritik Terhadap Impementasi Parliamentary Treshlod (Talenta Publisher, 2018)
This study raises a discussion about the Illusion of Substantial Democracy in Indonesia: A Criticism of the Implementation of Theshold's Parliamentary. Since the 2009 general election. Indonesia has begun to introduce a parliamentary threshold system (Parliamentary Theshold) which sets a 2.5% threshold. Then in the next election, the 2014 election rose to 3.5% in the spirit of simplifying the number of parties in parliament. However, in fact this did not happen. Because, the number of political parties resulting from the 2009 elections which were 9 parties actually increased to 10 parties in the 2014 election. There were other problems in the electoral system using Theshold Parliamentary. As in the 2009 elections there were 29 political parties whose voices were lost due to this system, then in the 2014 elections there were 2 political parties who also lost votes due to the threshold system. Of course, as a democracy the people must know where the voice is. Is the system of implementing the Theshold Parliamentary system in the Indonesian elections in line with the essence of substantial democracy? The results of this study indicate the parliamentary threshold system has an impact on the loss of the voice of small parties, transactional presidential elections and the parliamentary threshold limiting democratic rights. Indonesia needs an electoral system that is honest, free, high-quality, transparent and represents the wishes of the majority of Indonesia's ractates